2015
DOI: 10.11604/pamj.2015.20.24.4935
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of intracranial tumours in a tertiary health care facility: our findings

Abstract: IntroductionPrimary brain tumours are uncommon with an annual incidence of 5-10/100000. This study has attempted to analyse the histological pattern of intracranial tumours seen in our centre.MethodsA retrospective study of cases of intracranial tumours seen was conducted over a period of 5 years ie from January 2008 to December 2012. All the slides were reviewed. The age, sex, diagnosis using the WHO grading and the histological subtypes were recorded. Data were analysed using the (SPSS) Software version 17.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 10 publications
10
14
2
Order By: Relevance
“…17,18 Gliomas were the commonest tumour type, accounting for 38.2% of intracranial tumours followed closely by meningioma (36.2%). This is in keeping with findings in other studies 5,[7][8][9][10]17,18 Although gliomas are reported to be commoner in males, 3,5,7 there was a slight female preponderance in this study, which is similar to an earlier publication in Tema, Ghana by Andrews et al 12 This may be the true picture or just a trend suggesting that females tend to seek medical treatment more than men with similar conditions in Ghana.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…17,18 Gliomas were the commonest tumour type, accounting for 38.2% of intracranial tumours followed closely by meningioma (36.2%). This is in keeping with findings in other studies 5,[7][8][9][10]17,18 Although gliomas are reported to be commoner in males, 3,5,7 there was a slight female preponderance in this study, which is similar to an earlier publication in Tema, Ghana by Andrews et al 12 This may be the true picture or just a trend suggesting that females tend to seek medical treatment more than men with similar conditions in Ghana.…”
Section: Discussionsupporting
confidence: 92%
“…The total number of intracranial tumours seen over the study period showed female preponderance (see Table 1) similar to the findings by Soyemi SS et al 8 This is shown to be statistically significant (p= 0.031) in Table 2.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Only four patients had a tumor volume ≤50 cm 3 , and among these cases, three were independent at 1 year. Tumor size above 101-500 cm 3 had the most significant impact on outcome with 58.8% of the patients in this group dead within 1 year (P = 0.009). Patients with tumor volume above 50 cm 3 accounted for 94% of the mortality.…”
Section: Sizementioning
confidence: 92%